2019
DOI: 10.1111/imm.13093
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of PD‐1 follows tumour development in the AOM/DSS model of inflammation‐induced colorectal cancer in mice

Abstract: Summary Chronic inflammation may drive development of cancer as observed in inflammation‐induced colorectal cancer (CRC). Though immune cells can infiltrate the tumour microenvironment, cancer cells seem to evade anti‐tumour responses, which is one of the established hallmarks of cancer. Targeting the programmed cell death protein‐1 (PD‐1)/PD‐L1 signalling pathway is currently at the forefront in the development of anti‐tumour immunity‐based therapies for multiple malignancies. By blocking the immune‐checkpoin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 32 publications
3
25
1
Order By: Relevance
“… 18 The expression of PD-1 was upregulated on mucosal CD4, CD8αβ and TCRαβ cells of the colon and the ileum, which correlated with CAC progression. 43 Although the majority of CRCs with high CTLs infiltration have favourable outcomes, those with concurrently high PD-L1 gene expression have poor clinical outcomes. 44 In the present study, the proportion of PD-1 + CTLs was significantly reduced in CAC mice treated with pasteurised A. muciniphila or Amuc_1100.…”
Section: Discussionmentioning
confidence: 99%
“… 18 The expression of PD-1 was upregulated on mucosal CD4, CD8αβ and TCRαβ cells of the colon and the ileum, which correlated with CAC progression. 43 Although the majority of CRCs with high CTLs infiltration have favourable outcomes, those with concurrently high PD-L1 gene expression have poor clinical outcomes. 44 In the present study, the proportion of PD-1 + CTLs was significantly reduced in CAC mice treated with pasteurised A. muciniphila or Amuc_1100.…”
Section: Discussionmentioning
confidence: 99%
“…However, the ligand-receptor interaction can inhibit activity of PD-1 + TILs and silence the immune system [10]. Yassin et al have found that PD-1 is upregulated following tumor development and the increase of PD-1 expression is associated with tumor progression in inflammationinduced CRC in mice [11]. In addition, evidence has shown that high expression of PD-1 is associated with poor prognosis in primary central nervous system lymphoma (PCNSL) and esophageal cancer [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…In ILB ® , sulfur represents~17% of its total mass. While high molecular weight dextran sulfate possesses toxic effects, inducing cancer development and inflammation [31][32][33], ILB ® is a proven safe and well-tolerated LMW-DS. Previous studies showed that LMW-DS dose-dependently limits the instant blood-mediated inflammatory reaction (IBMIR) [34,35], inhibits E-selectin-mediated adhesion of neutrophils to endothelial cells [36,37], prevents adherence of peritoneal metastases [38], and improves the effectiveness of therapy and reduces mortality in patients with acute cerebral infarction treated with the thrombolytic agent urokinase [39].…”
Section: Introductionmentioning
confidence: 99%